Neural Mechanisms of Nonauditory Effects of Noise Exposure on Special Populations - Zixuan Xue; Xinran Ling; Xinru Zhao; Libo Geng (Noise and Health)
Due to the abnormal structure and function of brain neural networks in special populations, such as children, elderly individuals, and individuals with mental disorders, noise exposure is more likely to have negative psychological and cognitive nonauditory effects on these individuals. There are unique and complex neural mechanisms underlying this phenomenon. For individuals with mental disorders, there are anomalies such as structural atrophy and decreased functional activation in brain regions involved in emotion and cognitive processing, such as the prefrontal cortex (PFC). Noise exposure can worsen these abnormalities in relevant brain regions, further damaging neural plasticity and disrupting normal connections and the transmission of information between the PFC and other brain areas by causing neurotransmitter imbalances. In the case of children, in a noisy environment, brain regions such as the left inferior frontal gyrus and PFC, which are involved in growth and development, are more susceptible to structural and functional changes, leading to neurodegenerative alterations. Furthermore, noise exposure can interrupt auditory processing neural pathways or impair inhibitory functions, thus hindering children’s ability to map sound to meaning in neural processes. For elderly people, age-related shrinkage of brain regions such as the PFC, as well as deficiencies in hormone, neurotransmitter, and nutrient levels, weakens their ability to cope with noise. Currently, it is feasible to propose and apply coping strategies to improve the nonauditory effects of noise exposure on special populations based on the plasticity of the human brain.